THE INFLUENCE OF ENGLISH LEARNING THROUGH RECEPTIVE SKILLS AND PRODUCTIVE SKILLS ON THE LISTENING MATERIAL CAPABILITY - Sukma, Meita Maharani; Rochmawati, Laila; Fatmawati , Fatmawati; Kusumayati , Lusiana Dewi; Moonlight , Lady Silk (Fakultas Ilmu Pendidikan Universitas Negeri Surabaya, 2025)
Reflective learning is used to improve writing skills, and track the learning process regarding what students understand and what they do not understand. However, little research has explored the impact of reflective learning on students' critical thinking, especially in higher education. This study aims to fills the gap by exploring Indonesian EFL students in the seventh semester of using reflective learning in improving critical thinking skills and identifying their development of critical thinking skills through reflective learning. Questionnaires and students’ reflective learning are provided for data collection. The result reveal that from the questionnaire, reflective learning has an impact on students' critical thinking of 79.99%. Furthermore, it is also found that from students’ reflective learning participated in this study employed three development of critical thinking skills: 1) identify the strength, 2) recognize the weaknesses, and 3) find out the solution. Finding suggest that strategic use of reflective learning may enhance EFL critical thinking skills as well as maximize the achievement of their learning goals.